Colombia's Round Table on Sustainable Beef and implementation of the Policy Guidelines for Sustainable Cattle - Burkart, Stefan; Sandoval Yate, Danny Fernando; Diaz Baca, Manuel Francisco; Ángel, Natalia Triana (CGIAR System Organization, 2024)
"A key goal of the CGIAR Initiative on Livestock and Climate is improving the enabling policy environment by developing systems to improve the design and implementation of policies. Researchers also focus on building understanding and supporting the generation and sharing of knowledge. In Colombia, the Alliance of Bioversity and CIAT has been supporting the Colombian Roundtable for Sustainable Beef as a multistakeholder platform focused on transitioning Colombia towards more sustainable livestock production systems. A major success saw the consolidation of the Policy Guidelines for Sustainable Cattle in 2022 which have resulted in Colombia’s first national‐level policy for sustainable livestock (Resolution 126 of 2022). Currently however a lack of support and political will by the national government has meant implementation is not as successful as anticipated."